Emotional Intelligence and Teacher Efficacy as Predictors of Teacher Effectiveness among Pre-Service Teachers in Some Nigerian Universities - Agokei Roland-Alexander Chukwudi (International Journal of Evaluation and Research in Education (IJERE), 2014)
Evidence from teacher-effectiveness studies indicates that teacher effectiveness has yielded a wealth of understanding about the impact that teacher ability has on student growth. However, much is yet to be known on some psychological factors that could influence teaching effectiveness particularly among pre-service teachers. The purpose of the present study was to investigate the effect of emotional intelligence, and teacher efficacy, on the teacher effectiveness of pre-service teachers. Two validated instruments (Emotional intelligence scale; teacher efficacy scale) were administered on 300 students randomly selected from two Universities in the South-West region of Nigeria. Data were analysed using Pearson Product Moment Correlation and Multiple regression. The findings of this study demonstrated that emotional intelligence and teacher efficacy had predictive influence on teacher effectiveness. Based on these findings, it is suggested that appropriate strategies and policies for fostering teacher efficacy and emotional intelligence would go a long way in enhancing effective teaching among pre-service teachers.DOI: http://dx.doi.org/10.11591/ijere.v3i2.3858